The Flash. The complete first season [videorecording (DVD)] - Gustin, Grant, 1990-; Patton, Candice; Panabaker, Danielle (Warner Brothers Home Entertainment, 2015)
CSI investigator Barry Allen is endearingly book-smart, somewhat awkward late and, as a result of a scientific experiment gone awry, the fastest man alive. Zigzagging through the action-packed new series from the creative team behind Arrow and based on the supersonic DC Comics character. With his life shadowed by his mother's murder and his father wrongly convicted of the crime, Barry finds that his newfound power of super speed grants him the ability to move through Central City like an unseen guardian angel.